Analysis of Organizational Silence Attitudes of Hotel Operations’ Employees by Structural Equation Model: Examplary of Rize Province - Ali Caglar Gulluce; Eren Erkilic (European Scientific Journal, ESJ, 2016)
The objective of this research is to be able to identify the organization silence attitudes of the employees working at the hotels being operated in the city of Rize. For this purpose, questionnaire was applied to 228 employees functioning at the hotels. The data obtained have been analyzed with LISREL program. As a result of confirmatory factor analysis oriented towards determining the organizational silence behaviors of those who have taken part in the survey, favorable significant differences have been identified among the factors of organizational silence behavior. In this context, it has been determined that the most effective variable of "I think that my managers would not listen to my ideas" at a rate of .84 on the factors of Managerial and Organizational Reasons; at a rate of .83 on the factor of the Work – Related Topics "Public speaking can lead to loss of my job" variable; at the rate of .84 on the factor of Lack of Experience of “Since my position I am in is a lower level, my notification of an idea is disregarded” variable; at a rate of .84 on the factor of Isolation Factor “Reporting an issue may reduce confidence and respect felt to me" and at a rate of .87 on the factor of Fear Regarding Harming the Relationships “When I tell the problems, my relationships are damaged” variable. In addition, it has been observed that the Work – Related Topics factor had an influence at the rate of .93 between the factors of Fear of Isolation and Fear of Damaging the Relationships and the factors of Lack of Experience and Fear of Damaging the Relationships had an impact at the rate of .93 between each other.